Comparative Study: Implementation of Green Banking in Islamic Banks in Southeast Asia and Middle East Country - Bimantara, Andika Rendra; Naurah, Najwa Syifa; Nisa, Nurul Fauziatun (Universitas Muhammadiyah Surakarta, 2024)
This research aims to explore the implementation of green banking in Islamic banks across Southeast Asia and Middle East, utilizing the Green Coin Rating (GCR) tool, which encompasses six indicators: Carbon Emission, Green Rewards, Green Buildings, 3R (reuse, reduce, recycle), Paperless or Paperwork, and Green Investment. A comparative analysis was conducted on Bank Syariah Indonesia, Maybank, and Bank Islamic Brunei Darussalam from Southeast Asia, alongside Abu Dhabi Islamic Bank, Al-Rajhi Bank, and Meezan Bank from Middle East. The study evaluates the effectiveness of green banking initiatives across these institutions. The findings reveal that Southeast Asia outperforms Middle East in implementing green banking initiatives. Among the banks analyzed, Maybank achieved the highest GCR score, reflecting its strong commitment to sustainability through innovative green financing programs and carbon emission reductions. This research provides new insights into green banking practices in both regions and emphasizes the importance of cross-sector collaboration to achieve better sustainability outcomes. The results are intended to serve as a valuable reference for developing more effective and inclusive green banking policies in the future.